2020
DOI: 10.3390/nu12092651
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Beverage Consumption and Related Demographic Factors and Obesity among Korean Children and Adolescents

Abstract: It is well known that reducing consumption of sugar is a global public health priority. Beverages were the primary source of total sugar intake from processed foods. However, there are few studies investigating the trend of beverage consumption among children and adolescents in Korea. We examined the overall trend in beverage consumption among 11,996 participants aged 10–18 years who were enrolled in the Korea National Health and Nutrition Examination Survey (KNHANES) (1998–2018). Further, we examined the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 33 publications
(44 reference statements)
1
14
0
Order By: Relevance
“…Boys have reported to consume more beverages compared with girls (e.g. 6,40) . Moreover, girls may have substituted sugary soft drinks for diet soft drinks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Boys have reported to consume more beverages compared with girls (e.g. 6,40) . Moreover, girls may have substituted sugary soft drinks for diet soft drinks.…”
Section: Discussionmentioning
confidence: 99%
“…In childhood, eating habits are primarily moulded by the family environment, such as their parents' habits, education level and socioeconomic status (SES), whilst as a teenager, peers, mass media and an individual's own body image increasingly shape preferences, portion sizes and dieting habits (3) . In adolescence, food choices are increasingly characterised by less consumption of fruits and vegetables and greater consumption of soft drinks and snacks with a high-energy density such as that found in chips, candies and chocolate (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United States, the average caloric intake from SSBs among children aged 2~19 years increased from 204 in 1994 to 224 kcal/day in 2004, and then declined to 132.5 in 2014 [ 14 , 15 ]. In Korea, children and adolescents’ beverage intake steadily increased from 1998 to 2016~2018 [ 16 ]. A study from China covering 4 cities indicated that SSB consumption among 8–14-year-old children in urban areas increased from 329 to 715 mL/d from 1998 to 2008 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine-containing energy shots represent a new and relatively understudied area of nutrition [ 24 ]. In the present study we evaluated the metabolic impact of these small format beverages in adolescents, who represent key consumers of the products [ 25 ]. Very little is known about the metabolic effects of caffeine energy shot consumption in adolescents who by nature of the normal influences of puberty are generally more insulin resistant [ 26 ].…”
Section: Discussionmentioning
confidence: 99%